KERENTANAN WERENG BATANG COKELAT (NILAPARVATA LUGENS) DARI ENAM LOKASI DI PULAU JAWA TERHADAP TIGA JENIS INSEKTISIDA - Erwin Cuk Surahmat; Dadang .; Djoko Prijono (Universitas Lampung, 2016)
Susceptibility of the rice brown planthopper (Nilaparvata lugens) from six locations in Java to three insecticides. The rice brown planthopper (BPH), Nilaparvata lugens (StÃ¥l) (Hemiptera: Delphacidae), is one of the important rice pests in Indonesia. Despite relatively frequent use of insecticides to control this pest, data on BPH resistance to insecticides commonly used by farmers in Indonesia is scarce. This study was conducted to assess the susceptibility of BPH from six locations in Java to three insecticides, i.e. BPMC, imidacloprid, and pymetrozine, and to find out the historical use of insecticides by rice farmers. The first laboratory generations of BPH adults were subjected to insecticide treatments using a leaf dip residual method as described in IRAC Method No 005. Resistance factor (RF) for BPMC and imidacloprid was determined by comparing LC50 of each insecticide against BPH field populations with that against the reference population, whereas the susceptibility of BPH to pymetrozine was assessed based on inhibition of BPH population development. The three insecticides used in this study were commonly used by farmers in the six sampling locations and those insecticidesÂ were mostly used twice per rice growing season. BPH populations from all six locations as well as the reference population were susceptible to pymetrozine in which the treatment with pymetrozine at 50 ppm (one-fifth of the recommended field rate) caused 100% inhibition of BPH population development. BPH from five locations showed resistance to imidacloprid (RF > 4), but that from Pasuruan did not (RF 2.0). BPH from Indramayu was resistant to BPMC (RF 6.6) whereas those from the other five locations were not (RF < 4). Exposure of the reference population to a sublethal dose of insecticides (LC50 or IC50) decreased the susceptibility of the third BPH generation to pymetrozine and BPMC but not to imidacloprid.